Students’ perceptions of teacher performance in teaching: A case of university students - Trisnawati, Ika Kana; Helmanda, Cut Mawar; Saputri, Ardella (ACCENTIA: Journal of English Language and Education, 2023)
The study aimed to explore the university students’ opinions on teacher performance in terms of the instruction, motivation, and management during class. The study used a quantitative method, employing a questionnaire as the instrument to collect data. The participants of the study was 43 students majoring in English Education at a private university in Banda Aceh, Aceh, Indonesia. The study selected the participants by using random sampling. Data collected were analyzed by calculating the percentage. The results indicated that the students had positive opinions towards the instruction, motivation and management provided by their lecturers in the class. The study suggests that English instructors should provide proper instruction, motivation, and class management so that the students can become more enthusiastic in learning English within an engaging classroom.